Agephagy – Adapting Autophagy for Health During Aging - Stead, Eleanor R.; Castillo-Quan, Jorge I.; Miguel, Victoria Eugenia Martinez; Lujan, Celia; Ketteler, Robin; Kinghorn, Kerri J.; Bjedov, Ivana (Frontiers in Cell and Developmental Biology, 2019)
Autophagy is a major cellular recycling process that delivers cellular material and entire organelles to lysosomes for degradation, in a selective or non-selective manner. This process is essential for the maintenance of cellular energy levels, components and metabolites, as well as the elimination of cellular molecular damage, thereby playing an important role in numerous cellular activities. An important function of autophagy is to enable survival under starvation conditions and other stresses. The majority of factors implicated in ageing are modifiable through the process of autophagy, including the accumulation of oxidative damage and loss of proteostasis, genomic instability and epigenomic alteration. These primary causes of damage could lead to mitochondrial dysfunction, deregulation of nutrient sensing pathways and cellular senescence, finally causing a variety of ageing phenotypes. Remarkably, advances in the biology of ageing have revealed that ageing is a malleable process: a mild decrease in signalling through nutrient-sensing pathways can improve health and extend lifespan in all model organisms tested. Consequently, autophagy is implicated in both ageing and age-related disease. Enhancement of the autophagy process is a common characteristic of all principal, evolutionary conserved anti-ageing interventions, including dietary restriction, as well as inhibition of target of rapamycin (TOR) and insulin/IGF-1 signalling (IIS). As an emerging and critical process in ageing, this review will highlight how autophagy can be modulated for health improvement.